Pedestrian surveillance system based on mobile vehicle - Huijun XING; Shuo CHANG (Dianxin kexue)
Pedestrian surveillance is one of the most important aspects in the surveillance system.Traditional surveillance equipment can only cover the limit area.Namely,once the surveillance equipment is implemented,it can only monitor a specific region.Besides,the surveillance system can't detect if there is a person in the surveillance picture or not.The professional staffs are needed to determine whether there is a person in the surveillance picture.To solve this problem,a computer vision based on mobile pedestrian surveillance system was designed.By implementing a surveillance camera on a mobile small vehicle and remotely control it,the system could switch the monitoring area.Besides,the system could classify and locate the pedestrian in the picture with the deep convolutional neural network and correlation filters.Finally,the system was tested on the spot,which verified the feasibility of the system.